Study on the Effect of Processing Parameters on the Extraction of Stevioside Using Soxhlet Extractor - Normardhati, Mustafa (2012)
Stevioside can be obtained in Stevia rebaudiana leaves , which originated from Paraguay. It has been planted across Asia, Europe and Canada. It is the source of the highly sweet ent-kaurenoid diterpene glycosides, rebaudiana A, stevioside and other several sweet analogs. Stevioside is 300 times sweeter than sucrose and has lately gained importance as a natural non-caloric sweetener. The commercial exploration of S. rebaudiana has become stronger since 70’s due to the Japanese researchers developed extraction and purification process of sweetener. In S. rebaudiana, the ratio of stevioside to rebaudiaoside-A is 2:1. For its dominance, stevioside imparts a bitter after-taste characteristic to the crude extracts. The main purpose of this to study the effect of solvent concentration, extraction time and the ratio leaves to volume of solvent on the stevioside extraction. The soxhlet extractor was used in this study. Analysis of stevioside was carried out by anthrone reaction. From the results, extraction using 70% ethanol resulted in the highest stevioside yield at 12 mg/mL. Meanwhile, the highest stevioside at 16.5 mg/mL yield can be obtained during 24 hours extraction time. For the mass leaves to volume of solvent, 0.09g/mL of the mass of the leaves gave the highest stevioside yield at 32.5 mg/mL.